KELAYAKAN USAHATANI TANAMAN PORANG (Amorphophallus muelleri Blume) DI KABUPATEN TASIKMALAYA - Firmansyah, Sani; Nuryati, Rina; Noormansyah, Zulfikar (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2023)
One type of tuber plant that is currently being developed because it provides increased income for farmers is the porang plant (Amorphophallus muelleri Blume). This study aims to determine the production costs, revenues, income and financial feasibility of porang farming for one production process for 1 (one) year for an area of twenty five hectares. The research method used is a case study on porang farmers in Tasikmalaya Regency. The time of the research took place from February 2022 to May 2022. The data used consisted of primary and secondary data. The results showed that the production cost of porang farming was Rp. Rp. 4,434,353,000, - with a receipt of Rp. 7,906,236,000, - and an income of Rp. 3.471.883.000,-. The R/C value is 1.78, so this porang farming is financially feasible to continue.